Meige Trofoedema: A form of primary lymphedema - Salguero, Carlos Al Sanchez (Archives of Case Reports, 2018)
The lymphatic system consists of small non-contractile lymph vessels which collect fluid from the interstitial space and carry it to the major contractile lymphatic vessels with valves that maintain a unidirectional flow to the lymph nodes and is responsible for returning proteins, lipids and water from the interstitium to the venous system near the junction of the subclavian vein and internal jugular vein on both sides. Lymphedema would be the result of the failure of transport with the further accumulation of fluid rich in protein at the interstitium, especially in limbs. Primary lymphedema, which affects 1.15 / 100000 children (especially pre-pubescent girls), not always clinically evident at birth, is a genetic disorder that represents many different subsets of phenotypes: congenital or congenital lymphangiectasia, congenital trofoedema family or Meige, congenital amniotic band and essence or idiopathic. The most common form of presentation is due to congenital absence or abnormality of the lymphatic tissue caused by a genetic mutation of the genes responsible for the development of lymphatic vessels that is characterized by the difficulty of draining lymph vessels. This genetic alteration may be sporadic or inherited.